Study the effect of different pretreatments on thin layer drying of grape and the color of obtained raisin - Azam Ayoubi; Naser Sedaghat; Mehdi Kashaninejad (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2015)
The purpose of this research was to study the effect of thin layer drying conditions (temperature at three levels of 60,70, and 80 oC, air velocity at two levels of 1/5 and 2/5 m/s, and four pretreatments including potassium carbonate and Paksan drying oil, olive oil, hot water without pretreatment (control)) on cabinet drying process of grape and color of obtained raisin. Six mathematical models were fitted on drying data and the best one was selected according to coefficient of determination (R2), Root Mean Square Error (RMSE) and coefficient of relative average deviation (P). The results showed that temperature, air velocity and pretreatment have significant effects on drying rate and color of raisin. Among these models, two term and page models showed more ability to evaluating and describing drying behavior of grape. Diffusion coefficient values were between 4/6274×10-10 to 8/6541×10-10 m/s2 and activation energy obtained 13470/83 J/mol. The best values of lightness and redness were related to dried raisin at 60 oC and the maximum value of yellowness was related to dried raisin at 70 oC. Drying air velocity just significantly affected the redness. Increasing drying air velocity decreased the redness. It was also found out that potassium carbonate and Paksan drying oil pretreatment caused the best raisin color.